EFFECT OF LEVERAGE, COMPANY SIZE, GROWTH COMPANY AND PROFITABILITY ON COMPANY VALUE IN PROPERTY COMPANIES LISTED ON THE STOCK EXCHANGE INDONESIA (IDX) 2017-2021 - Sarnilika Laia; Rejeki Putra Jaya Waruwu; Wirda Lilia; Elina Rahmawati Gustarina (SEAN Institute, 2023)
This study aims to determine the relationship between profitability, leverage, and the composition of the board of commissioners, audit committee, fiscal loss compensation for tax evasion in banking companies that are registered on the IDX in 2017 - 2019. The research method used is a quantitative research method with a descriptive approach. The research population is 39 companies. The sampling technique used is purposive sampling. Based on the results of the study indicate that Partially Profitability has a positive effect on tax avoidance, but leverage, the composition of the board of commissioners, audit committees, and compensation for fiscal losses has an effect on tax avoidance. The results of the study simultaneously show that the variables of profitability, leverage, composition of the board of commissioners,